2006
DOI: 10.1002/ajh.20797
|View full text |Cite
|
Sign up to set email alerts
|

Megakaryocytic blast crisis as first presentation of chronic myeloid leukemia

Abstract: We describe an extremely rare case of megakaryocytic blast crisis as first presentation of chronic myeloid leukemia. The patient had a very high platelet count and developed an ischemic stroke with seizures. She was treated with hydroxyurea, platelet apheresis, ARA-C, and idarubicin in order to obtain a prompt reduction of thrombocytosis and then with imatinib 600 mg/die PO. The therapy induced a complete hematological remission with a resolution of neurological signs within 4 weeks. Am. J. Hematol. 82:231-233… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Myelofibrosis or increased bone marrow reticulin are a prominent aspect in most AMKL patients. In some cases, megakaryoblastic crisis could be the first presentation of CML, and not distinguishable from de novo AMKL [12-16]. This case represents de novo AMKL in our opinion, because the patient had no basophilia and eosinophilia upon presentation, which are often seen in blast crisis of CML [17].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Myelofibrosis or increased bone marrow reticulin are a prominent aspect in most AMKL patients. In some cases, megakaryoblastic crisis could be the first presentation of CML, and not distinguishable from de novo AMKL [12-16]. This case represents de novo AMKL in our opinion, because the patient had no basophilia and eosinophilia upon presentation, which are often seen in blast crisis of CML [17].…”
Section: Discussionmentioning
confidence: 89%
“…Cytogenetic analysis of trypsin R-banded chromosome preparations revealed 46, XX, der(16)t(1;16)(q21;q23)[8]/46,XX [12] (Figure 2). To identify fusion genes, multiplex reverse transcription-polymerase chain reaction (RT-PCR) was performed with 1~8 parallel nested (2-round) multiplex reactions in a thermocycler (Perkin-Elmer) to achieve maximal sensitivity, as described in a previous study [11].…”
Section: Case Presentationmentioning
confidence: 99%
“…Megakaryocytic blast crisis as the presenting manifestation of CML is rare. Previous studies (11,12,19), with the exception of a study by Westfall et al (20), have shown that imatinib has good effects on patients with a megakaryocytic blast crisis of CML. However, the in vitro effect of exposure to imatinib on the proliferation or apoptosis of CD34 + cells from patients with CML in the megakaryocytic crisis phase has not been described.…”
Section: Discussionmentioning
confidence: 93%
“…Rarely, patients with CML can present directly in a blast crisis. While most blast crises are of myeloid origin, myeloid blast crisis with ALL‐like morphologic features and Ph‐positive AML is rare, especially at the time of CML diagnosis . This is the first case of CML blast crisis presented with AML of t(9;22) and t(3;14) double translocation mimicking ALL.…”
Section: Introductionmentioning
confidence: 95%